"Mesenteric stripping using a Veress needle: A creative approach to resect small bowel disease in advanced ovarian cancer" - Joao Casanova; José Filipe Cunha; Sara Proença; Dennis Chi (Elsevier, 2023)
Small bowel involvement in patients with advanced ovarian cancer has been associated with a worse prognosis and recent data suggests it can be an independent factor associated with shorter disease-free interval (Casales Campos et al., 2022). In the upfront cytoreductive setting, small bowel residual disease (serosa and mesentery) has been identified as the most common site of residual disease (Heitz et al., 2016). The morbidity associated with multiple small bowel resections and the length of the remaining small bowel constitute major limiting factors. As the surgical armamentarium of the gynecologic oncologist has considerably broaden to include more radical procedures, addressing miliary small bowel disease remains extremely important in the quest to achieve complete gross resection (CGR) and thus improving the overall prognosis (Jurado and Chiva, 2021). We present a case of a patient with stage IIIC high grade serous ovarian carcinoma that already had started neoadjuvant chemotherapy before presenting for surgical options. After 4 cycles of carboplatin and paclitaxel, the patient was offered interval cytoreductive surgery plus HIPEC with cisplatin. During surgical exploration, miliary small bowel mesenteric disease was noted but with a grossly intact jejunoileal serosa. The patient underwent bilateral diaphragmatic stripping, cholecystectomy, extraperitoneal hysterectomy and multiple parietal peritonectomies. A decision was made to perform a mesenterectomy using a Veress needle. A standard insuflator was utilized to a maximum pressure of 4 mmHg. CGR was achieved and the patient underwent HIPEC as per institution protocol. The post operative course was uneventful and the patient was discharged five days after surgery. She is currently free of disease (20 months after surgery).